Avaliação ambiental por geoprocessamento na sub-bacia do Rio Angasmarca, Região la Libertad, Peru - Rimarachin, Jorge Luis Diaz (2012)
The agricultural activities, without considering the potential and limitations on the land use, are a potential source of environmental degradation. This study proposed the environmental diagnose of the sub-basin Angasmarca river, in La Libertad region in Peru, using geoprocessing techniques. For the execution of the work were incorporated into a Geographic Information System (ArcGIS 9.2) data obtained by remote sensing (CBERS multispectral image and ASTER DEM G-2 digital elevation model), topographic maps, rainfall data, soil analyzes and thematic maps existing (geology, soils, ecology). From the morphometric characterization of the study area, we obtained the potential use of land (from the roughness coefficient) characterizing areas liable to degradation by environmental conflicts and identify areas susceptible to laminar erosion supported in Equation Universal Soil Loss (USLE). From the analysis of hydrologic conditions and soils of watersheds evaluated by the circularity index (CI), compactness coefficient (Kc) and form factor (Kf), the region is favorable to processes of runoff, but nevertheless not subject to floods. In the evaluation of potential soil use, it was found that 33.18% of the sub-basin is appropriate for agricultural practice, 52.12% for pasture, 9.45% for pasture/forestry and 5.25% for forestry. 50.88% (17963.53 ha) of the total area of the sub-basin is in use conflicts therefore requires adaptations that reduce environmental degradation. In the analysis of rainfall erosivity was found that the annual average value (EI30) is 4.762 MJ.mm.ha-1.h-1.year-1 (R factor), with a monthly average of the 396.8MJ.mm.ha-1.h-1. In the rainy season (October to April) was 4678.5MJ.mm.ha-1.h-1 (considered erosive) and the dry season (May to September) of 83.5MJ.mm.ha1.h-1 (considered non-erosive). Therefore the estimates soil losses upper than 97.82t.ha-1.year-1 area located in the watersheds with the greater slopes (88.88km²), however, the watersheds with the lowest soil loss area (mean 77.47t.ha-1.year-1 76.92 km2) area located on flatter land. The mathematical modeling performed in the Geographic Information System enabled the integration data of the estimates of erosion potential laminar and environmental assessment Physical- Conservationist, permitting spatialize areas the potential risk both conflicts of land use, erosion and environmental deterioration, the which allows to propose mitigation actions for areas that present the biggest problems.